Does the Age of Board Members Affect Firms' Financial Performance? A Case of ESG Leader Companies in Indonesia - Rusadi, Gisyla Oktaviana; Zen, Tuntun Salamatun (Integrasi Sains Media, 2023)
A lot of scholars across the globe have attempted to investigate the effects of board diversity towards firms’ financial performance and yielded inconclusive results. In this paper, the author aims to discover the effects of one of the board diversity attributes on firms’ financial performance in Indonesia, namely age diversity (measured by standard deviation) as well as the variables surrounding the board members' ages (average age and the presence of millennials). Purposive sampling method is used to select the research sample, which resulted in 41 companies which are listed in the ESG Sector Leaders IDX KEHATI index. The time frame of the observation is from 2018 to 2022. By using panel data regression, the author finds out that age diversity on BOC has a positive relationship with ROA, average age of BOC has a negative relationship with ROE, while the presence of millennials on BOD & BOC combined has a positive relationship with ROA. The negative association between average age and ROE indicates that boards with a younger average age outperform boards with an older average age. However, interestingly, the board members' age does not have any significant effect on the financial performance indicator which reflects the market perspective as measured by Tobin's Q.